(untitled) (Revista Argentina de Cirugía, 2021)
Background: Different scenarios have emerged with the advent of minimally invasive approaches; transoral endoscopic parathyroidectomy vestibular approach (TOEPVA) is a technique with promising results. Objective: The aim of this study is to describe the surgical technique and the experience gained. Material and methods: We describe 3 patients with asymptomatic primary hyperparathyroidism due to parathyroid adenoma and one case of tertiary hyperparathyroidism with parathyroid hyperplasia with clinical signs and presence of lesions in imaging tests. Results: In 3 patients operative time was 202.5 minutes. The patients had adequate tolerance to pain and remained hospitalized for 24 hours. One patient with ectopic parathyroid adenoma required conversion to open surgery that was complicated with an accidental esophageal injury. Intraoperative parathormone levels decreased by >50% compared by baseline values in all the cases. Conclusions: This minimally invasive procedure is reproducible but should be used in selected cases as it is not free of complications.